Tiruaruṭpā - Ramalinga, Swami, 1823-1874 (Irāmaliṅkar Paṇimaṉṟam, 1981)
Complete works of a Tamil religious poet and founder of Samarasa Suddha Sanmarga, Hindu syncretic religious movement; chronologically arranged.